Penerapan Manajemen Risiko Dalam Keuangan Proyek Sumber Daya Air Di Era Perubahan Iklim: Studi kasus Bendung Tugusari - Suhuliah, Suhuliah; Lilis Putri Nufia Sari; Dimas Fitrianto; Denari Dhahana Edtiyarsih; Sri Irawan Laras Prasojo (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The Tugusari Dam has a strategic role in water resource management, especially for irrigation and flood control. However, climate change presents a range of risks, including increased extreme rainfall, sedimentation, and project financial uncertainty. This study analyzes the application of financial risk management in this project with a qualitative approach using the Delphi method and the Probability Impact Matrix (PIM). The results of the analysis showed that 10 out of 19 risk variables were classified as medium, while the other 9 were significant. Key risks include design changes, project delays, rising material costs, and labor and equipment uncertainty. This study recommends a mitigation strategy based on a comprehensive risk management system to improve the efficiency and sustainability of projects in facing the challenges of climate change